1968
DOI: 10.1037/h0026556
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shifts in sucrose and saccharine concentrations on licking behavior in the rat.

Abstract: To study effects of shifts in concentration of liquid reinforcers on licking behavior 4 experiments were performed. Depressed performance (relative to control groups) accompanied a shift from 32% to 4% sucrose solutions, but not a shift in saccharine concentrations. Various bases for this disparity were investigated, including type of deprivation and levels of deprivation. Depression in licking appears to result from shifts in sucrose concentration, with larger depressions accompanying increased amounts of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
1

Year Published

1971
1971
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 10 publications
4
45
1
Order By: Relevance
“…The major research finding was that hippocampal Ss show a rapid and appropriate adjustment to increases in incentive and an undershooting of control levels following a reduction of incentive (a NCE). This result is the standard response pattern seen following reward shifts (Black, 1968;Vogel, Mikulka, & Spear, 1968). These findings are not consistent with the results reported by Murphy and Brown (1970), using a very similar research design.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The major research finding was that hippocampal Ss show a rapid and appropriate adjustment to increases in incentive and an undershooting of control levels following a reduction of incentive (a NCE). This result is the standard response pattern seen following reward shifts (Black, 1968;Vogel, Mikulka, & Spear, 1968). These findings are not consistent with the results reported by Murphy and Brown (1970), using a very similar research design.…”
Section: Discussioncontrasting
confidence: 56%
“…However, these Ss do show the typical magnitude of reward effects during the preshift-acquisition phase. In contrast, Murphy and Brown (1970), using a licking response, found rapid behavioral adjustment to a decreased reward, but failed to find any evidence of the well-documented negative contrast effect (NCE; Black, 1968;Vogel, Mikulka, & Spear, 1968)_ Murphy and Brown also found that the same Ss did not display any preference for varying sucrose concentrations in preference tests, but did respond appropriately during the preshift phase.The present experiment was conducted fo examine the effects of dorsal hippocampal lesions on lick rates after reward shifts. The lesions used in this study were considerably more localized than the complete hippocampal aspirations used by Franchina and Brown (I 971) and Murphy and Brown (1970)_ Furthermore, this design used a symmetrical shift paradigm, while Murphy and Brown (I970) only shifted their Ss to lower reward levels.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…a phenomenon that don't fit Thorndike's classic law of effect (Herrnstein, 1970;Thorndike, 1911), which predicts an association between behavior and its consequences. This rupture can be clearly perceived when individuals are exposed to a surprising devaluations in the reward quality or quantity received in response to instrumental (Crespi, 1942) or consummatory behavior (Vogel, Mikulka & Spear, 1968). In a typical SNC experiment, a group of rats receives a 32% sucrose solution in a 5-min-long sessions for 10 days (preshift) and then are presented with a 4% sucrose solution in 5-min-long sessions for 5 days (postshift).…”
Section: Introductionmentioning
confidence: 99%
“…This decrement in performance, termed a negative contrast effect, has been found in a wide variety of experimental situations and with a variety of rewards. For example, contrast has been obtained in runways with shifts in amount of food (e.g., Crespi, 1942, DiLollo & Beez, 1966, in complex mazes with shifts to qualititatively different foods (e.g., Elliott, 1928), in free-operant paradigms with shifts in schedule of reinforcement (e.g., Reynolds & Limpo, 1968), and in simple consummatory response situations in" which the shift has been to a lower concentration of sucrose solution (e.g., Flaherty, Capobianco, & Hamilton, 1973;Vogel, Mikulka, & Spear, 1968).The occurrence of a contrast effect implies that the animal is, in some sense, comparing the new reward with the old, and the outcome of this comparison influences the animal's behavior. One question of interest that arises concerning contrast effects relates to the conditions under which this comparison will be made.…”
mentioning
confidence: 99%